Estudo do desempenho de um conversor de energia tipo coluna de água oscilante utilizando um modelo computacional tridimensional e design construtal com três graus de liberdade - Bloss, Vinícius (Universidade do Vale do Rio dos Sinos, 2020)
Recently, the oceans have been seen as a promising source of renewable energy. Theoretically, the oceans could offer enough energy to supply the entire world demand. Among the technologies available for energy conversion from the oceans, the Oscillating Water Column (OWC) type devices stand out, which are characterized by a chamber, in which the water oscillates inside in a movement similar to a piston. This movement moves the air to a chimney, where a turbine is attached. The passage of air through the turbine promotes the conversion into mechanical energy. In the present work, the study of the performance of a 1:15 scale OWC type converter was performed using a three-dimensional computational fluid dynamics model. The analysis was based on the Constructal Design Method. In this approach, energy is the quantity that flows through the system, whose purpose is the maximum rate of conversion of wave energy into mechanical energy. Three degrees of freedom were used: the ratio of height to length of the hydropneumatic chamber (H1/L), the ratio of the height of the chimney to its diameter (H2/d), and the ratio of the width of the hydropneumatic chamber to the width of the wave tank (W/Z). The effect of different combinations between degrees of freedom for a typical wave of the southern region of the Brazilian coast was investigated. Conversion efficiency was used as a performance parameter. Computational modeling of the system was performed, using computational fluid dynamics software based on the finite volume method (FVM), using the Volume of Fluid (VoF) modeling for the interface between the gas and liquid phases. In a first analysis, it was observed that the height of the chimney always has a positive effect on the efficiency of the system. However, only workable values were selected for this degree of freedom, limiting the subsequent analyzes to two degrees of freedom, H1/L and W/Z. Through a Design Experiment of the Central Composite Project type, different combinations of degrees of freedom were simulated, allowing the construction of Response Surfaces and correlations for the efficiency of the system depending on the degrees of freedom width and height of the chamber, as well as the optimization of the system based on the Response Surfaces. In the tests carried out, the efficiency of the OWC device varied from 1.48% to 19.32% in the worst and best case, respectively.
Keywords: Design construtal; Fluidodinâmica computacional; Conversor de energia das ondas; Coluna de água oscilante; Construtal design; Computational fluid dynamics; Wave energy converter; Oscillating water column; ACCNPQ::Engenharias::Engenharia Mecânica